Yangi Oʻzbekiston pedagoglari axborotnomasi. 1-jild, 9-son (YOʻPA).: Those who seek paradise from a different land are partial. - Soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2024)
Only works that caused a lot of hype in the history of Uzbek literature of the 20th century. For its time of Shukhrat, the novel “Those who seek Paradise” about the ancient theme – the without hometown part is among such works that it can be judged as a masterpiece of writer. With the creation of this novel, writer deserves in his time a rather great appreciation for the compressions of the Soviet totalitarian regime, the fact that in some way he dared to challenge